2016
DOI: 10.1002/ijc.30249
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes after umbilical cord blood and unmanipulated haploidentical hematopoietic stem cell transplantation in children with high‐risk acute lymphoblastic leukemia

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) is an effective therapy for children with high-risk acute lymphoblastic leukemia (ALL). Human leukocyte antigen (HLA)-haploidentical HSCT (haplo-HSCT) or umbilical cord blood transplantation (UCBT) are both important alternative sources of stem cells for those without an HLA-identical sibling donor or unrelated matched donor. We aimed to compare the therapeutic effects of single UCBT and unmanipulated haplo-HSCT in high-risk ALL children (n = 129). Hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 44 publications
5
41
0
1
Order By: Relevance
“…Despite the possible GVL effect, cGVHD was reported to have an adverse effect on NRM41 and was the main cause of poor quality of life after transplantation 42. However, low probability of cGVHD has always been one of the advantages of CB,43 and many studies reported that the relapse rate in CBT was similar to or lower than in other kinds of HCT,44, 45, 46 which reflected the clinical separation of cGVHD and the GVL effect in CB. Furthermore, our previous study showed that long‐term survivors with CBT had less cGVHD and higher quality of life compared to HCT in HLA‐identical sibling's donors 47.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the possible GVL effect, cGVHD was reported to have an adverse effect on NRM41 and was the main cause of poor quality of life after transplantation 42. However, low probability of cGVHD has always been one of the advantages of CB,43 and many studies reported that the relapse rate in CBT was similar to or lower than in other kinds of HCT,44, 45, 46 which reflected the clinical separation of cGVHD and the GVL effect in CB. Furthermore, our previous study showed that long‐term survivors with CBT had less cGVHD and higher quality of life compared to HCT in HLA‐identical sibling's donors 47.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary transplantation practice involving the use of double cord blood units in case that there are not enough stem cells in a single cord, flexible conditioning regimens, effective graft-versus-host disease (GvHD) prophylaxis platforms with non-T cell depleted (NTD) Haplo, and improved management of post-transplant complications, have brought improvement in outcomes of alternative donor transplantations [3, 7, 12]. Several studies have reported that results with UCBT and Haplo are comparable with those of transplants from HLA identical or matched unrelated donors [1322]. …”
Section: Introductionmentioning
confidence: 99%
“…In view of the fact that haploidentical HSCT (haplo-HSCT) can provide all patients with a potential donor, it has become an important alternative choice for many VHR ALL children when undergoing transplantation in recent years. In our previous study, we demonstrated the safety and efficacy of haplo-HSCT in the treatment of paediatric VHR ALL (Mo et al, 2016). However, as far as we know, no study has compared the efficacy of intensive chemotherapy and haplo-HSCT as post-remission therapy in paediatric VHR Ph-negative B-ALL, and the role of haplo-HSCT for post-remission therapy in these patients is not well established.…”
Section: Discussionmentioning
confidence: 99%